ANALISIS IMPULS BUYING PADA KONSUMEN CHANDRA SUPER STORE TANJUNG KARANG - Yunada Arpan; Rina Magdalena S (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2018)
This study aims to analyze the effect of price discounts and display of shelves on impulsepurchases on consumers Chandra Super Store Tanjung Karang. The population in this study is thevisitors who shop at Chandra Super Store with an infinite number of consumers. Sampling techniqueusing probability sampling method by using simple random sampling with the number of samples of 100people. Data collection techniques used questionnaires that have been tested for validity and reliability,and data analysis techniques used are multiple regression.Based on the results of research and testing simultaneously (test f) obtained Fhitung 45,007 >Ftable 3.09 it can be interpreted the discount and rack display significantly affect the purchase ofimpulse at consumers in Chandra Super Store Tanjung Karang and based on partial test (t test)obtained value Thitung variable discount price of 5.939 > ttable 1.660, and for display rack obtained tcount of 5.202 > ttabel 1.660. In the variable of research result obtained coefficient of determination (R2)equal to 0,481 indicate that impulse purchasing influenced by price cut and display rack equal to 48,1%,while rest 51,9% influenced by other factors outside factor studied. While the relation of price discountand shelf display together to purchase consumer impulse, then get regression equation Y = 3,248 +0,459bX1 + 0,519bX2.